Photoinduced Decarboxylative Amino‐Fluoroalkylation of Maleic Anhydride. Issue 2 (5th December 2019) - Sun, Youwen; Zhang, Guozhu
Abstract: A photoinduced decarboxylative three‐component coupling reaction involving amine, maleic anhydride, and fluorinated alkyl iodides has been developed, leading to synthetically valuable fluoroalkyl‐containing acrylamides with a high E selectivity. A broad array of substrates including monoprotected amino acid are capable coupling partners. Preliminary mechanistic studies suggest a stepwise process. This reaction represents the first example of photoinduced decarboxylative difunctionalization of maleic anhydride. Abstract : Go photo ! A photoinduced decarboxylative three‐component coupling reaction involving amine, maleic anhydride, and fluorinated alkyl iodides has been developed, leading to synthetically valuable fluoroalkyl‐containing acrylamides with a high E selectivity. A broad array of substrates including monoprotected amino acid are capable coupling partners. Preliminary mechanistic studies suggest a stepwise process.